Gellan-gum and LiTFSI-Based solid polymer electrolytes for electrochromic devices - Isfahani, Vahideh Bayzi (2021)
It has been long recognized that solid polymer electrolytes (SPEs) are potentially interesting for solid-state electrochemical devices. Gellan gum (Ge)-based SPEs, plasticized with glycerol (Gly) and doped with lithium bis(trifluoromethanesulfone)imide (LiTFSI) were prepared by the solvent casting technique, and their properties were evaluated. LiTFSI-based SPE systems exhibit, on the average, higher conductivities than similar systems with other lithium salts. The structure, morphology, complex impedance spectroscopy, cyclic voltammetry and thermal stability of the new electrolyte system were characterized. Electrochromic devices (ECDs) were built with optimized electrolyte samples and their performance was analyzed. The samples were applied in small ECDs with glass/ITO/CeO2-TiO2/SPE/Prussian blue/ITO/glass configuration. The devices presented a two-modulation operation: a semi-bright mode (-2.5 V) and a dark mode (+0.5 V). The best results were obtained with the ECD containing the GeGly(1)Li(2.4) electrolyte, for which the transmittance (T) values in the bleached and colored states were ca. 33.4/43.0 % and 5.4/8.8 % at 555/1000 nm, respectively. These results correspond to Delta T and Delta OD values of 28.0/34.2 % and 0.79/0.69, respectively, which give quite high CEin and CEout values of -4925 cm(2) C-1 for bleaching (Q(in)=-272.1 mu C cm(-2)), and 2062 cm(2) C-1 for coloring (Q(out)=650.0 mu C cm(-2)), at 630 nm. This electro-optical performance suggests that the proposed SPE systems are promising materials to be further investigated and applied in ECDs.